Effect of cold-work on the Hall–Petch breakdown in copper based micro-components - Ghassemali, Ehsan (2016)
Effects of substructural dimensions on the mechanical properties of micro-pins produced by an open-die micro-extrusion/forging process were studied. Micro-pins of diameter 0.3 mm were manufactured from copper strips, having different initial grain sizes. Micro-compression tests on the micro-pins revealed no significant size effect, even if the number of grains over the diameter of the micro-pins falls below its critical value. However, relaxation of the as-formed substructure using recovery annealing led to a surprising drop in the flow stress of the micro-pins. This was explained and attributed to the number of subgrains over the diameter of the micro-pins, showing the important role of subgrains rather than grains in determining the mechanical properties.